In situ phosphonium-containing Lewis base-catalyzed 1, 6-cyanation reaction: a facile way to obtain α-diaryl and α-triaryl acetonitriles. Issue 1 (26th November 2021) - Tan, Jian-Ping; Chen, Yuan; Ren, Xiaoyu; Guo, Yumeng; Yi, Bing; Zhang, Hongkui; Gao, Guowei; Wang, Tianli
Abstract : A in situ phosphonium-containing catalyst and its successful application in promoting remote 1, 6-cyanation reaction of p -QMs and fuchsones have been disclosed, providing a facile and direct access to both α-diaryl and α-triaryl acetonitriles. Abstract : We present a phosphonium-containing catalyst generated in situ from phosphine and tert -butyl acrylate that serves as an unusual Lewis base catalyst. It was applied for the promotion of a remote 1, 6-cyanation reaction of p -quinone methides and fuchsones employing trimethylsilyl cyanide as the cyanide source. A diverse range of α-diaryl and α-triaryl acetonitriles was obtained in high yields under mild reaction conditions with low catalyst loading (5 mol%). The practicality and utility of this protocol were demonstrated via the gram-scale preparation and facile elaboration of products. Mechanistic investigations ( in situ NMR and ESI-MS analysis) were employed to characterize the active zwitterionic phosphonium intermediate, which was the "true" active catalyst.